Hardware developments of an ultrasonic tomography measurement system - Hudabiyah, Arshad Amari; Ruzairi, Abdul Rahim; Mohd Hafiz, Fazalul Rahiman (International Frequency Sensor Association (IFSA), 2011)
Link to publisher's homepage at http://www.sensorsportal.com/